Conceptual framework - von Braun, Joachim; Bouis, Howarth E.; Kennedy, Eileen T. (International Food Policy Research Institute, 1994)
In this chapter, the basic theoretical relationships and definitional issues related to the commercialization of agriculture and described. Simply speaking, cash crops can be defined as crops for sale. The listing of typical agricultural processing enterprises in chapter 9 gives a rough overview of cash crops (also, see von Braun and Kennedy 1986). Yet, commercialization of agriculture as a process and a characteristic of agricultural change is more than whether or not a cash crop is present to a certain extent in a production system. Commercialization of subsistence agriculture and take many different forms.